2008
DOI: 10.2460/ajvr.69.8.1022
|View full text |Cite
|
Sign up to set email alerts
|

Relative expression of matrix metalloproteinase-2 and -9 in synovial fluid from healthy calves and calves with experimentally induced septic arthritis

Abstract: Results indicated that relative expression of MMP-9 and MMP-2 increased in synovial fluid from calves with experimentally induced septic arthritis, with relative expression remaining high for several days after infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…In cattle, higher activity in milk has also been reported after endotoxin-induced mastitis and in synovial fluid after an experimentally induced septic arthritis (Raulo et al, 2002;Francoz et al, 2008). Furthermore, MMP-9 can be covalently linked to Hp and released as MMP9-Hp complexes by neutrophils when their degranulation occurs.…”
Section: Other Biomarkers That Could Have Potential To Detect Sepsismentioning
confidence: 97%
“…In cattle, higher activity in milk has also been reported after endotoxin-induced mastitis and in synovial fluid after an experimentally induced septic arthritis (Raulo et al, 2002;Francoz et al, 2008). Furthermore, MMP-9 can be covalently linked to Hp and released as MMP9-Hp complexes by neutrophils when their degranulation occurs.…”
Section: Other Biomarkers That Could Have Potential To Detect Sepsismentioning
confidence: 97%
“…Well-controlled bovine lameness induction models are scarce in the published literature. Models based on intraarticular inoculation of bacteria are difficult to standardize and control, and often cause intense and prolonged pain (Francoz et al, 2008). Amphotericin B, a polyene antibiotic, produces a controlled, mild to moderately severe synovitis-arthritis of short duration (Fahmy et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Arican et al found increased concentrations of MMP-9 activity in the synovial fluid of cows with septic arthritis in comparison with fluids from normal joints, using gelatin zymography and ELISA [2]. Two more animal studies confirmed the above data in horses and calves [7,9]. Two more animal studies confirmed the above data in horses and calves [7,9].…”
Section: Discussionmentioning
confidence: 79%
“…It is possible that pro-MMP-9, activated by bacterial acids, plays a crucial role in joint destruction [9]. It is possible that pro-MMP-9, activated by bacterial acids, plays a crucial role in joint destruction [9].…”
Section: Discussionmentioning
confidence: 99%